Contemporary management of abdominal surgical emergencies in infants and children. Issue 1 (29th November 2013) - van Heurn, L W E; Pakarinen, M P; Wester, T
Abstract: Background: Acute abdominal complaints in children are common presentations in the emergency department. The aetiology, presentation, diagnosis and management often differ from those in adults. Methods: This review was based on expert paediatric surgical experience confirmed by evidence from the literature obtained by searching PubMed and the Cochrane Library. Keywords used were the combinations of 'abdominal emergencies', 'acute abdomen' and the disorders 'acute appendicitis', 'intussusception', 'volvulus', 'Meckel's diverticulum', 'incarcerated inguinal hernia', 'testicular torsion' and 'ovarian torsion' with 'children'. Information was included from reviews, randomized clinical trials, meta-analyses, and prospective and retrospective cohort studies. Results: Presentation and symptoms of abdominal emergencies, especially in young children, vary widely, which renders recognition of the underlying disorder and treatment challenging. Critically targeted imaging techniques are becoming increasingly important in obtaining the correct diagnosis without unnecessary delay. Minimally invasive techniques have become the method of choice for the diagnosis and treatment of many abdominal emergencies in children. Conclusion: Knowledge of abdominal disorders in childhood, their specific presentation, diagnosis and treatment facilitates management of children with acute abdomen in emergency departments. Imaging and minimally invasive techniques are becoming increasingly important in the diagnosis of acute abdomen in children. Urgent operation remains the cornerstone of therapy for most acute abdominal disorders. Abstract : Useful to know about children